Legal Accountability and Policy Gaps in Social Engineering-Based Phishing Cybercrimes - Purwadi; Makhfud, Mukhamad; Jamaludin, Ahmad (LifeSciFi, 2025)
Social engineering-based phishing is increasingly rampant in Indonesia, exploiting victims' psychological weaknesses to access illegal and spread false information. The main legal problem is the imperfection of regulations, such as the ITE Law and the Criminal Code, which do not accommodate the psychological manipulation aspect of this crime. This study aims to identify regulatory gaps related to the legal responsibility of phishing perpetrators and the effectiveness of regulations in dealing with this crime. The method used is normative juridical, with analysis of laws and regulations, literature studies, and reviews of court decisions. The findings show that the ITE Law focuses more on technical-based crimes, while the psychological aspect of phishing has not been explicitly regulated. failed to prove the perpetrator's intent (dolus) is an obstacle to law enforcement. The implication of this study is the need to revise the ITE Law to expand the scope of